PEMBERDAYAAN UMKM DESA LENGGAHSARI MELALUI EDUKASI PEMBUKUAN KEUANGAN - Nur Evita Bela; Purnama Putra; Rizal Fahlevi (LPPM Universitas Islam 45, 2023)
MSMEs play a role as a source of income for the community, fulfilment of goods and services, creation of jobs, and increasing added value so as to reduce poverty and economic growth. However, there are also crucial problems that are often found in MSME actors in Indonesia, namely the problem of financial bookkeeping. This is due to the fact that there are still many MSME actors who have not implemented financial bookkeeping in the businesses they run. In Lenggahsari Village, it is known that the dominant population works as farmers and traders. Many MSME players in Lenggahsari village who have run their businesses still have not implemented financial bookkeeping in the businesses they run. Therefore, the implementation of community service is carried out with the aim of increasing the understanding of MSME actors to implement a financial bookkeeping system so that business records run well. The method used in this service applies the method of community socialisation and training. The results of community service show that MSME actors already have a good understanding of the financial bookkeeping system and business operations.